Local government policymaking environment for Health in All Policies: a case study research investigation - Lilly, Kara; Robinson, Suzanne; Selvey, L.A.; Hallett, Jonathan (2024)
The local level of government is identified as being well placed to address the determinants of health due to their flatter governance structure and proximity to the community. Research has identified multiple factors that influence local governments to act on these health determinants, although few have applied theories of the policy process to understand the policymaking environment. Using two Australian local government case study sites, we explored the policymaking environment regarding policy decisions to address health determinants using the lens of four theories of the policy process. We conducted 20 interviews and one focus group with elected members and staff in local government, along with an analysis of 12 policy documents and participation in a policy reference group. Following thematic analysis, 13 factors influencing policy addressing health determinants were identified, mostly confirming previous research from within Australia and globally. New themes have emerged regarding the limited range of policy actors involved and the lack of advocacy, particularly by community or media, who have an identified influence over decision-making in a local government context. Applying theories of the policy process also demonstrates how they can be used to add meaning to the interconnectedness of influences in unique local government policymaking environments.